A honfoglalás, a kónstantinosi Turkia és az Ajtony-törzs - Tóth Sándor László (Monográfiák a Szegedi Tudományegyetem Régészeti Tanszékéről, 2017)
The study examines the settlements of the Hungarian (Magyar) tribes in two periods. The first period can be put between 900 and 950, when the Hungarian tribes settled in the Carpathian Basin. The Byzantine emperor, Constantine VII (944–959) described the Hungarian territory called by him Turkia in five chapters in his famous compilation, De administrando imperio. In chapter 40, the territory of the Turks (Hungarians/Magyars) is described with different methods. The Byzantine emperor identified the Hungarian settlement with the earlier Moravia (Great or Old Moravia), named five rivers (Temes, Tutis, Maros, Körös, Tisza) north of the river Danube, and mentioned four neighbours of the Hungarians (Pechenegs, Bulgars, Franks and Croatians). It can be argued, that this description of Turkia derives from the report of cleric Gabriel, who visited the Hungarians at the first decade of the 10th century. Emperor Leo VI (Wise) wanted the Hungarians to reoccupy their earlier settlements from the Pechenegs, but the Hungarian tribal chiefs angrily refused the offer. According to other chapters of Constantine, the Hungarians had settlements not only east of the Danube, but west of it (Pannonia) as well. Ibn Hayyan also mentioned the nomadic settlements of the Turks (Hungarians) near the Danube. In the second period, at about the foundation of the Christian state by king Stephen (first decade of the 11th century), there are sources (legend of Saint Gerard, Anonymus) from the 13th and 14th centuries, that refer back to the vast territory of Ajtony, between the river of Körös or Maros and the Danube. Ajtony was probably the leader of the Kavar (Kabar) tribes, and was defeated by the army of king Stephen. His territory can be identified with the ’Turkia’ of emperor Constantine, the district of the five rivers, the region of river Tisza.